The Social Geography of Diphtheria Mortality in Hamilton - Battles, Heather; Jones, Bobbie-Leigh (Ontario History, 2018)
This Hamilton, Ontario today displays stark socioeconomic disparities in health which pattern along north/south lines within the city. Diphtheria provides a useful lens for examining the historical nature of these socioeconomic disparities. Data were collected from death registrations for the period 1900 to 1921 and 321 deaths were mapped in ArcMap. Diphtheria mortality rates were higher in the north overall; however, no difference was found for the 5–16 year age group (school age). Higher mortality in children under age five in the north due to factors associated with low SES may explain the differing rates. These results demonstrate the social inequalities in health that existed in early-twentieth century Hamilton and their geographic dimension.